Scientific Rigor Level of Master’s Thesis in Education - Case Study: Public University - Chambi Mescco, Edith (2017)
The present research had as objective to identify, through evaluation, scientific rigor level ofthe masters’ theses in education of a public university. We used the documentary analysistechnique; an instrument was made to evaluate the master´s thesis and was validated by theexperts judgment technique. The population was made of a total of 126 master’s thesespublished between the years 2012 and 2014, and of a quantitative type, a sample of 72master’s theses were taken for analysis applying stratified sampling per year publicationand were selected randomly. We evaluated each of the theses that were obtained from theEducation Faculty Library. We evaluated each of the theses that were retrieved from theEducation Faculty Library and we identified to what level they belonged on a scale of five:high, very high, medium, low and very low. After the descriptive statistical analysis, we candetermine that most of the theses correspond to the average level of Scientific Rigor.